Mastering English Pronunciation: A Comprehensive Guide Using the ELSA Speak App for Enhancing Fluency - Luri Dini Ayu; Laila Wati; Hajriana Arfah; M Adib Nazri (Departement of Mathematics Education, 2024)
The objective of this study was to assess the efficacy of the ELSA talk application in facilitating pronunciation instruction. The study focused on a tenth-grade student enrolled at SMA Islam Darul Mujahidin NWDI Majidi during the 2024 academic year, which had a total of 18 pupils. This study utilized a pre-experimental research design, specifically a one-group pre-test and post-test design. The researcher employed pre-test and post-test instruments to get the data. The data in this study was analyzed using SPSS 22 for Windows. The researcher conducted the treatment over the course of four meetings. The analysis revealed that the average score after the exam was higher than the average score before the test (77.22>50.83), and the hypothesis was confirmed (t(z) = -3.756 at p = 0.000). It was reported that the treatment effectively enhanced students' pronunciation skills. The study determined that the utilization of the